2018
DOI: 10.1002/nau.23554
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐1 adrenergic antagonists, 5‐alpha reductase inhibitors, phosphodiesterase type 5 inhibitors, and phytotherapic compounds in men with lower urinary tract symptoms suggestive of benign prostatic obstruction: A systematic review and meta‐analysis of urodynamic studies

Abstract: ABs and 5-ARIs efficiently improve BOOI in men with LUTS/BPO. Both treatments are associated with a clinically significant decrease in PdetQmax but only marginal improvements in Qmax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 38 publications
0
18
0
1
Order By: Relevance
“…However, further studies are needed to confirm these observations. Indeed, given the concomitant bladder outflow benefits and a favourable safety profile, there is a compelling rationale for the prospective evaluation of 5-ARIs as a secondary prevention strategy for BCa recurrence in men [ 31 , 32 , 33 ]. Although androgen suppression has the potential of being a means of radio- and chemiosensitization, further studies are needed to confirm this preclinical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are needed to confirm these observations. Indeed, given the concomitant bladder outflow benefits and a favourable safety profile, there is a compelling rationale for the prospective evaluation of 5-ARIs as a secondary prevention strategy for BCa recurrence in men [ 31 , 32 , 33 ]. Although androgen suppression has the potential of being a means of radio- and chemiosensitization, further studies are needed to confirm this preclinical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Though it is assumed that prostate smooth muscle contraction is induced by activation of α 1 ‐adrenoceptors, hyperplastic prostate stromal cell growth is mediated by dihydrotestosterone 1,2 . For immediate improvement of symptoms α 1 ‐blockers are often applied, whereas 5α‐reductase inhibitors have long‐term effects through reduction of prostate size 1,3 . Around 612 million men worldwide were affected by LUTS secondary to BPH in 2018, with annual costs peaking up to five billion USD for medical treatment 4–6 .…”
Section: Introductionmentioning
confidence: 99%
“…One more crucial limitation in our study is that several studies among final included studies for meta-analysis do not have clinically significant BOO, which could resulted in lowering efficacy of 5ARI during meta-analysis. Moreover, recent meta-analysis about the efficacy of 5ARI in BOO has showed that BOOI reduction is important clinical outcomes during BPH/LUTS treatment [ 10 ]. Lastly, network analysis among alpha blocker, 5ARI, and placebo are needed to suggest the direct evidence of inferior clinical efficacy of 5ARI compared to alpha blocker.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, treatment using 5ARIs showed a positive effect including decreased prostate volume, improved International Prostate Symptom Score (IPSS), improved Qmax, decreased risk of acute urinary retention (AUR) and decreased operative procedures related with BPH/LUTS [ 5 , 7 9 ]. Moreover, several systematic reviews showed that 5ARI, especially, finasteride improves LUTS by long-term treatment, however, combination treatment with alpha blockers showed better improvement than finasteride monotherapy [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%